The specificity of vesicle traffic to the Golgi is encoded in the golgin coiled-coil proteins - Wong, Mie; Munro, Sean (Science (American Association for the Advancement of Science), 2014)
The inside of the cell contains a large variety of different membrane transport vesicles, each of which needs to find and fuse with its correct target destination. The detailed mechanism specifying which vesicle can fuse with which target membrane has been the subject of an enormous amount of research. An additional layer of specificity in intracellular membrane trafficking across the Golgi complex is thought to involve particular membrane “tethers.” However, the importance of these tethers has been unclear. Wong and Munro used a clever trick to reveal how specific tethers can indeed ensure correct vesicle destination. Tether proteins experimentally expressed on mitochondria hijacked different transport vesicles and diverted them from their normal destination to the mitochondria. Science , this issue 10.1126/science.1256898 Specific proteins can tether and distinguish between specific intracellular transport vesicles in vivo. The Golgi apparatus is a multicompartment central sorting station at the intersection of secretory and endocytic vesicular traffic. The mechanisms that permit cargo-loaded transport vesicles from different origins to selectively access different Golgi compartments are incompletely understood. We developed a rerouting and capture assay to investigate systematically the vesicle-tethering activities of 10 widely conserved golgin coiled-coil proteins. We find that subsets of golgins with distinct localizations on the Golgi surface have capture activities toward vesicles of different origins. These findings demonstrate that golgins act as tethers in vivo, and hence the specificity we find to be encoded in this tethering is likely to make a major contribution to the organization of membrane traffic at the Golgi apparatus.